Perspectivas acerca do niilismo na Genealogia da moral - Pacheco, Juarez de Oliveira (2013)
By analyzing the concept of nihilism, which is shown polysemic in Nietzsche's work, we encounter frequent deadlocks concerning the origin of this phenomenon. This concept usually presents signifying a consequence of the moral development of the West, where the slave resentment and bad conscience, rooted in culture, ends up affecting modern man of a weariness and an emptying of value: it is nihilism in its own sense, a phenomenon of modern origin. On the other hand, there are aphorisms and excerpts, least discussed by the German philosopher in his work, indicating that the origin of nihilism refers to a distant period of human history, preceding the Christian moral-ascetic, and a phenomenon that opens a gap of absence of meaning about life and human suffering. These incompatible aspects of nihilism are present both in print, and in private notes of Nietzsche. The interior of the book Genealogy of Morals also holds that ambiguity of the concept of nihilism. The main objective of this work is to investigate the work Genealogy of Morals, with the help of other texts, trying to understand the meanings of nihilism and position in the history of civilization. Nietzsche s work as objects of study presents the concepts of resentment and bad conscience ascetic ideal, elements that are constitutive of Western morals. With interests in its topicality, Nietzsche investigates the past moral to its prehistory. Thus, this work is fundamental research into the origin of nihilism. His concepts are analyzed from a procedure that puts them in the realm of historical development and the dynamics instinctual, while concepts that change over time and have multiple meanings: with this polysemic feature that the central elements of the work are presented as well as nihilism. The Genealogy of Morals finally reveals that nihilism has various meanings, but that does not necessarily clash with each other. We show in this work a form of nihilism primordial, a "first nihilism" that is precedent-Christian ascetic morality, including that operates as one of the causes of this moral. However, nihilism is presented as historical product of peacemaking mechanisms of civilization, which inevitably leads to poor awareness and resentment. Human instincts turn inward, causing a great malaise of civilization in the form of a long suffering baseless. The ascetic priest gives an answer to this suffering, reverses the direction of resentment, bad conscience reinterpreting the animal, making it more serious, in a way defined as the interpretation of suffering for sin. The bad conscience made man suffer senseless with instincts that turned against him, however, with the ascetic interpretation, now he unloads his forces against them with a sense that justifies the suffering.